2022
DOI: 10.1039/d2cp00567k
|View full text |Cite
|
Sign up to set email alerts
|

Beyond structural insight: a deep neural network for the prediction of Pt L2/3-edge X-ray absorption spectra

Abstract: X-ray absorption spectroscopy at the L2/3-edge can be used to obtain detailed information about the local electronic and geometric structure of transition metal complexes. By virtue of the dipole selection...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…orbital information) should be included explicitly in the feature vector alongside the nuclear structural information is a natural one and, at present, one that requires further investigation. Watson et al [110] demonstrated that there remains a sufficiently strong implicit link between geometric and electronic structural information to develop a sufficiently accurate ML model at the Pt L 2/3 edges using a purely geometric feature vector viathe wACSF representation. The authors noted, however, that the error in the ML XAS spectral predictions was largest close to the L 2/3 absorption edges, i.e.…”
Section: On the Explicit Inclusion Of Electronic Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…orbital information) should be included explicitly in the feature vector alongside the nuclear structural information is a natural one and, at present, one that requires further investigation. Watson et al [110] demonstrated that there remains a sufficiently strong implicit link between geometric and electronic structural information to develop a sufficiently accurate ML model at the Pt L 2/3 edges using a purely geometric feature vector viathe wACSF representation. The authors noted, however, that the error in the ML XAS spectral predictions was largest close to the L 2/3 absorption edges, i.e.…”
Section: On the Explicit Inclusion Of Electronic Informationmentioning
confidence: 99%
“…Figure 2 illustrates that x-ray spectra are typically broad in comparison to, for example, optical and vibrational spectroscopies. Consequently, the calculated spectra must be transformed by incorporating factors including core-hole-lifetime broadening and instrument response [110,133] to enable them to be compared to the experiment. An example of the influence this has is shown in figure 6 and can be added as a pre-processing or post-processing step in the ML models.…”
Section: Representing X-ray Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, attempts have been made to predict spectra from molecular structures using machine learning models, and there have been several reports: prediction from molecular graphs using a message passing graph neural network (GNN), 12 a deep neural network, [13][14][15] and prediction using neural network ensemble through featurized local structural information. 16 However, as far as the authors know, the prediction of core electron excitation spectra considering anisotropy according to the momentum transfer has not been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed 21,22 and deployed [25][26][27] a deep neural network (DNN) -XANESNET 28 -for predicting the lineshape of X-ray absorption (XAS) 21,22,29 and emission (XES) 23 spectra. XANESNET predicts spectral lineshapes using only local information about the coordination geometry of the absorbing atom.…”
Section: Introductionmentioning
confidence: 99%